Anesthesia for Cesarean Delivery in the Czech Republic. (June 2015) - Stourac, Petr; Blaha, Jan; Klozova, Radka; Noskova, Pavlina; Seidlova, Dagmar; Brozova, Lucie; Jarkovsky, Jiri
<x xml:space="preserve">Abstract</x> BACKGROUND: The purpose of this national survey was to determine current anesthesia practices for cesarean delivery in the Czech Republic. METHODS: In November 2011, we invited all departments of obstetric anesthesia in the Czech Republic to participate in a prospective study to monitor consecutive peripartum obstetric anesthesia procedures. Data were recorded online in the TrialDB database (Yale University, New Haven, CT). RESULTS: The response rate was 51% (49 of 97 departments); participating centers represented 60% of all births in the country during the study period. There were 1943 cases of peripartum anesthesia care, of which 1166 cases (60%) were anesthesia for cesarean delivery. Estimates were weighted based on population distribution of cesarean delivery among types of participating centers. Neuraxial anesthesia was used in 55.6% (95% confidence interval [CI], 52.8%–58.5%); the distribution of anesthesia techniques differed among type of participating center. The rate of neuraxial anesthesia in university hospitals was 55.6% (95% CI, 51.5%–59.6%), 32.4% (95% CI, 26.4%–39.0%) in regional hospitals, and 60.7% (95% CI, 55.2%–66.0%) in local hospitals. The reasons for cesarean delivery under general anesthesia were emergency procedure (67%), refusal of neuraxial blockade by parturient (30%), failure of neuraxial anesthesia (6%), and preoperative administration of low-molecular-weight heparin (3%). Postcesarean analgesia was primarily provided by systemic opioid (66%) and nonopioid analgesics (61%), solely or in combination. Epidural postoperative analgesia was used in 14% of cases. Compared with national neuraxial anesthesia rate data published in the 1990s (6.7% in 1993), there has been an upward trend in the use of neuraxial anesthesia for cesarean delivery during the 21st century (40.5% in 2000) in the Czech Republic. CONCLUSIONS: The rate of neuraxial anesthesia use for cesarean delivery has increased in the Czech Republic in the last 2 decades. However, the current rate of general anesthesia is high compared with other Western countries.